An Investigation of Organizational Culture, Workplace Partnership and its Supply Chain Role for Sustainable Employment Relations in Public Universities in Malaysia - Badariah Ab Rahman; Dzurizah Ibrahim; Rosazman Hussin; Jabil Mapjabil; Zikri Muhammad; Jumadil Saputra (International Journal of Supply Chain Management, 2020)
The organizational culture is different to every businesses and company. It aims to provide employees with a guiding principle on the work and organization system and a sense of direction by achieving organizations aspirations. Thus, the purpose of this study is to investigate the organizational culture and workplace partnership for achieving sustainable employment relations at public universities in Malaysia. This study is designed using a qualitative approach through observation and interviews. This study reveals that a loose organizational culture and partnership arrangement existed between the Academic Joint Consultative Committees (JCC) management and vice versa. The finding established that the desire to move forward is being felt however still concerned with whom the authority in decision making. This research argues that the management will continue to make final decisions; thus will preserve its supremacy as the single authority in public universities in Malaysia. The result warrants some amendments toward the organizational culture and workplace partnership in preserving industrial harmony. This study recommends a new form of organizational culture and workplace partnership for sustainable employment relations for a better working environment.Keywords— organizational culture, workplace partnership, decision making, consultation